Antishear Stress Bionic Carbon Nanotube Mesh Coating with Intracellular Controlled Drug Delivery Constructing Small‐Diameter Tissue–Engineered Vascular Grafts. Issue 11 (10th April 2018) - Ding, Ning; Dou, Ce; Wang, Yuxin; Liu, Feila; Guan, Ge; Huo, Da; Li, Yanzhao; Yang, Jingyuan; Wei, Keyu; Yang, Mingcan; Tan, Ju; Zeng, Wen; et al.
Abstract: Small‐diameter (<6 mm) tissue–engineered blood vessels (TEBVs) have a low patency rate due to chronic inflammation mediated intimal hyperplasia. Functional coating with drug release is a promising solution, but preventing the released drug from being rushed away by blood flow remains a great challenge. A single‐walled carboxylic acid functionalized carbon nanotube (C‐SWCNT) is used to build an irregular mesh for TEBV coating. However, an interaction between the released drug and the cells is still insufficient due to the blood flow. Thus, an intracellular drug delivery system mediated by macrophage cellular uptake is designed. Resveratrol (RSV) modified CNT is used for macrophage uptake. M1 macrophage uptakes CNT‐RSV and then converts to the M2 phenotype upon intracellular RSV release. Prohealing M2 macrophage inhibits the chronic inflammation thus maintains the contractile phenotype of the vascular smooth muscle cell (VSMC), which reduces intimal hyperplasia. Additionally, RSV released from the mesh coating also directly protects the contractile VSMCs from being converted to a secretory phenotype. Through antishear stress coating and macrophage‐based intracellular drug delivery, CNT‐RSV TEBVs exhibit a long‐term anti‐intimal hyperplasia function. Animal transplantation studies show that the patency rate remains high until day 90 after grafting in rat carotid arteries. Abstract : A bionic carbon nanotubes (CNTs) mesh structure coating is developed for small‐diameter tissue engineered blood vessels (TEBVs). Resveratrol (RSV) was crosslinked with CNTs for macrophage uptake and intracellular drug release. Through anti‐shear stress coating and macrophage based intracellular drug delivery; CNT‐RSV TEBVs exhibited a long‐term anti‐intimal hyperplasia function via maintaining the contractile phenotype of vascular smooth muscle cells (VSMCs).